2019
DOI: 10.1080/20020317.2019.1688451
|View full text |Cite
|
Sign up to set email alerts
|

Parental school satisfaction in the context of segregation of basic education in urban Finland

Abstract: This article examines the implications of the school choice policy, which has contributed to the segregation of basic education in urban Finland, by analysing the connection between the socio-economic status (SES) of schools' student populations and parents' satisfaction with their children's schools. The 318 participants were parents of lower secondary school students attending socio-economically affluent, average, and disadvantaged schools in three Finnish cities. Multiple indicators multiple causes modellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 79 publications
(138 reference statements)
0
6
0
Order By: Relevance
“…In addition, parents may not be fully aware of their children's interactivity on the Internet (Beale & Hall, 2007). Thus, studies claim that the safety of children is the most significant predictor of parent satisfaction (Friedman et al, 2007;Tikkanen, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, parents may not be fully aware of their children's interactivity on the Internet (Beale & Hall, 2007). Thus, studies claim that the safety of children is the most significant predictor of parent satisfaction (Friedman et al, 2007;Tikkanen, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Such parents are unconcerned with a specific result and are more focused on the happiness and mental peace of their child (Frijns, Keijsers, Branje, & Meeus, 2010). Similarly a study from Finland showed that parents were content with their child's school satisfaction and learning (Tikkanen, 2019). Whereas, literature from Abu Dhabi showed a lower percentage; 35% in regard to parents satisfaction with their children's grades (Guang, Badri, Al Rashedi, & Almazroui).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Public service organisations have also recognised the importance of customer satisfaction as a strategic imperative, taking advantage of its potential to address their ineffectiveness and improve their overall performance (Ananda et al, 2023). In the context of education services, where marketisation has emerged as a prominent concern, parent satisfaction is viewed as a strategic tool to address the growing competition between schools and obtain more favourable evaluations (Tikkanen, 2019).…”
Section: 3mentioning
confidence: 99%